A voyage through turbulence - Davidson, P. A. 1957-; Kaneda, Yukio, 1947-; Moffatt, H. K. 1935-; Sreenivasan, Katepalli R., 1947- (Cambridge University Press, 2011)
"Turbulence is widely recognized as one of the outstanding problems of the physical sciences, but it still remains only partially understood despite having attracted the sustained efforts of many leading scientists for well over a century. In A Voyage Through Turbulence we are transported through a crucial period of the history of the subject via biographies of twelve of its great personalities, starting with Osborne Reynolds and his pioneering work of the 1880s. This book will provide absorbing reading for every scientist, mathematician and engineer interested in the history and culture of turbulence, as background to the intense challenges that this universal phenomenon still presents"--Resumé vydavatele
Keywords: turbulentní proudění; proudění tekutin; dynamika tekutin; fyzici; dějiny fyziky; turbulent flow; liquid flow; fluid dynamics; physicists; history of physics; populárně-naučné publikace; popular works